The value of ultrasonography and computerized tomography in estimating the histopathological severity of nonalcoholic steatohepatitis - Ataseven, H; Yildirim, MH; Yalniz, M; Bahcecioglu, IH; Celebi, S; Ozercan, IH (Univ Catholique Louvain-Ucl, 2005)
Background & Aims : Liver biopsy is the gold standard for the diagnosis of non-alcoholic steatohepatitis (NASH), but is an invasive method. There is a need for non-invasive methods that can reflect the histopathological severity of NASH. The aim of this study was to compare the ultrasonography and computerized tomography findings with the histopathological severity in patients with NASH. Material and Methods : Twenty-two consecutive patients with biopsy proven NASH and 20 age- and sex-matched healthy individuals were enrolled. Clinical and demographic data were collected at the time of, liver biopsy. Histopathological grading and staging were made by an expert pathologist. Each patient underwent ultrasonography and computerized tomography. Results : Liver ultrasonographic findings were not correlated with histopathological grade and stage (r:0.134, P>0.05; r:0.130, P>0.05). Mean liver densities obtained by computed tomography of NASH patients were lower than that of controls (P<0.05) and liver/spleen density ratios were lower than that of controls (P<0.05). These results were significantly correlated with histopathological grade (r:-0.716, P<0.001; r:-0.663, P:0.001), but not with the histopathologic stage (r:-0.416, P:0.05; r:-0.356, P:0.1). Conclusions : Ultrasonography findings do not reflect histopathological severity in patients with NASH. Computed tomography attenuation of the liver is significantly correlated with histopathologic grade but not with histopathological stage.
Keywords: nonalcoholic steatohepatitis; histopathology; ultrasonography; computerized tomography